The tat/rev intron of human immunodeficiency virus type 1 is inefficiently spliced because of suboptimal signals in the 3' splice site. - Staffa, A (1994)
Proportional expression of retroviral genes requires that splicing of the viral primary transcript be an inefficient process. Much of our current knowledge about retroviral suboptimal splicing comes from studies with Rous sarcoma virus. In this report, we describe the use of chimeric introns composed of human beta-globin and human immunodeficiency virus type 1 (HIV-1) splice sites to establish the basis for inefficient splicing of the intron which comprises most of the HIV-1 env coding sequences (referred to as the tat/rev intron). S1 RNA analysis of transfected COS-7 cells revealed that the 3' splice site (3' ss) of this region was significantly less efficient than the 3' ss of the first intron of beta-globin. Deletion of sequences flanking the tat/rev intron 3' ss demonstrated that the requirements for its inefficiency reside within the region that is expected to comprise the essential signals for splicing (i.e., the branchpoint region, the polypyrimidine tract, and the AG dinucleotide). Introduction of an exact copy of the efficient beta-globin branchpoint sequence within a highly conserved region rendered the tat/rev intron 3' ss highly efficient. Improvement of the polypyrimidine tract also increased the splicing efficiency, but to a degree slightly less than that obtained with the branchpoint mutation. Subsequent examination of the tat/rev intron 5' splice site in a heterologous context revealed that it is efficiently utilized. These results indicate that both a poor branchpoint region and a poor polypyrimidine tract are responsible for the low splicing efficiency of the HIV-1 tat/rev intron. It is of fundamental interest to establish the basis for inefficient splicing of the HIV-1 tat/rev intron since it may provide the key to understanding why nuclear export of mRNAs encoding HIV-1 structural proteins is Rev dependent.